Dimensional crossover in bose-hubbard model. - Zhang, Zhifeng. (2011)
We used quantum Monte Carlo simulation to investigate the dimensional crossover in the Bose-Hubbard model when the inter layer coupling Jp was reduced from 1 to 0. In particular, the evolution of the superfluid transition was studied. We found that the critical temperature of phase transition decreases monotonically with Jp and the system started to have a 2-D behavior when Jp < 0.04. The critical temperature eventually converged to the critical temperature (Tc = 0.79(1)) of the 2-D Berezinsky-Kosterlitz- Thouless transition. The dimensional crossover was observed.